Analyzing students' perception towards higher education amenities in a public university in Terengganu / Zildawarni Irwan ... [et al.] - Irwan, Zildawarni; Mohd Akhir, Noor Erni Fazlina; Rani, Norhamimah; Zakaria, Noorul Huda (Universiti Teknologi MARA, Terengganu, 2016)
Provision of quality services is one of the most important priorities in higher education institutions. This quality comes from the combination of excellent learning process and students' satisfaction on the service delivered. Positive perception or acceptance on quality of services is vital to ensure the sustainability of higher learning. Therefore, this study aims to analyze students' perception towards amenities provided by a public university in Terengganu. The amenities investigated in the study consisted of lecture rooms, laboratory, cafeteria, hostel, vehicle and traffic, and electricity and water supply. The primary data of this study was collected using questionnaires. Participants of the study consisted of 108 students who were randomly selected. The study revealed that students' perceptions towards amenities provided were average with the score mean value 4.62. The students agreed that the lecture rooms provided by the university are mostly conducive and comfortable. However, the students were mostly not satisfied with the cafeteria. Thus, it is hoped that the finding of the study can give insights to the public university management to improve the amenities towards achieving sustainability of campuses.